Correlation between Leukocyte Esterase and the Incidence of Preterm Birth and Maternal and Neonatal Outcomes - Adi Pramono; Lies Ani Tambunan; Setyorini Irianti (Indonesian Journal of Obstetrics & Gynecology Science, 2026)
Objective: Leukocyte esterase (LE) is a diagnostic marker for urinary tract infections (UTIs), the management of which may mitigate the risk of preterm labor and neonatal complications. This study evaluates the correlation between positive LE, preterm labor, and subsequent infant outcomes.Methods: This retrospective cohort study at Hasan Sadikin General Hospital analyzed medical records of singleton pregnancies in 2024. Using total sampling and multivariable logistic regression, the study evaluated the correlation between maternal urinalysis with positive leukocyte esterase, the incidence of preterm birth, and 5-minute APGAR scores.Results: Of the 420 patients analyzed, preterm labor occurred in 60.5% of cases. Positive LE was identified in 42.1% of the cases. Multivariate analysis revealed that positive LE significantly increased the risk of preterm delivery (aOR = 1.57, p = 0.042). However, positive LE was not a significant determinant of neonatal asphyxia (OR = 0.97, p > 0.999), which demonstrated a stronger association with lower birth weight and infrequent antenatal care visits. Conclusion: Maternal leukocyte esterase positivity is associated with approximately a 1.5-fold increase in the likelihood of preterm labor. Conversely, no significant association was observed between LE levels and neonatal asphyxia or 5-minute APGAR scores.Hubungan antara Leukosit Esterase dengan Kejadian Persalinan Prematur dan Luaran Ibu dan BayiAbstrakTujuan: Leukosit esterase membantu mendiagnosis Infeksi Saluran Kemih (ISK), yang berpotensi mengurangi risiko persalinan prematur dan asfiksia kelahiran. Penelitian ini bertujuan menganalisis korelasi antara leukosit esterase, persalinan prematur, dan hasil bayi.Metode: Studi kohort retrospektif yang dilakukan di Rumah Sakit Hasan Sadikin melalui data rekam medik, dilakukan total sampling pasien dengan kehamilan tunggal pada tahun 2024. Data dianalisis dengan uji Chi square, dilanjutkan dengan regresi logistik multivariat untuk mengevaluasi hubungan antara hasil urin leukosit esterase positif dengan persalinan prematur, dan skor APGAR 5 menit.Hasil: Dari 420 pasien, persalinan prematur terjadi pada 60,5% kasus. Leukosit Esterase (LE) positif ditemukan pada 42,1% kasus persalinan prematur. Analisis multivariat menunjukkan bahwa LE positif secara signifikan meningkatkan risiko persalinan prematur (aOR = 1,57; p = 0,042). Namun, hal tersebut bukan merupakan penentu signifikan bagi asfiksia neonatal (OR = 0,97; p > 0,999), yang justru lebih kuat dikaitkan dengan berat badan lahir rendah dan kunjungan perawatan antenatal (antenatal care) yang lebih sedikit.Kesimpulan: Leukosit esterase positif meningkatkan risiko persalinan prematur sekitar 1,5 kali lipat, namun tidak menunjukkan hubungan signifikan dengan asfiksia neonatal atau skor APGAR 5 menit.